Intranasal vaccination with a Chimeric Chlamydial Antigen BD584 confers protection against Chlamydia trachomatis genital tract infection - Steven Liang; James B Mahony (Journal of Vaccines and Immunology - Peertechz Publications, 2020)
Chlamydia is the most common sexually transmitted infection of bacterial origin, and a broadly protective vaccine is urgently needed given the largely asymptomatic nature of the infection and the severe reproductive sequelae in women with untreated infections. The primary aim of this study was to characterize the immune response to vaccination with BD584, a novel recombinant antigen consisting of three type III secretion (T3S) proteins, and to evaluate its efficacy against a Chlamydia trachomatis challenge in three strains of mice. C57BL/6, BALB/c, and C3H/HeN mice were vaccinated three times intranasally with BD584 and CpG adjuvant, then challenged intravaginally with C. trachomatis. BD584/CpG vaccination induced strong cell-mediated and humoral immune responses in all three strains of mice, suggesting that this vaccine should be immunogenic in a genetically heterogenous population. BD584/CpG vaccination reduced vaginal shedding of C. trachomatis in C57BL/6 and C3H/HeN mice. Together, these results strengthen the rationale for further investigating the use of T3S proteins in a C. trachomatis vaccine.